Referral Hire Presence Implications for Referrer Turnover and Job Performance - Pieper, Jenna R.; Trevor, Charlie O.; Weller, Ingo; Duchon, Dennis (Journal of Management, 2019)
A great deal of research has been devoted to understanding the organizational returns of employee referral programs, particularly with respect to outcomes involving those hired through the referral process. Yet, no work has addressed whether the presence of a referral hire (i.e., the referred candidate who is hired and working in the firm) is related to behavioral outcomes for the referrer. Drawing on the social enrichment perspective, we theorize how referral hire presence (RHP), which is the time during which the referrer’s and the referral hire’s employment spells overlap, impacts referrer behavior. Using data from 265 referrers in a U.S. call center, we found that RHP was negatively related to referrer voluntary turnover and positively related to referrer job performance. Further, results from a supplemental experimental study supported our social enrichment rationale for the field study relationships, as the construct was associated with both RHP and additional attitudes known to be proximal predictors of turnover and performance. We also explore boundary conditions for the RHP effect in the call center data, revealing a nuanced mix of moderators of RHP effects. Overall, our findings provide the first evidence for the role of social enrichment, possible modifications to the well-established social enrichment perspective in the workplace, and evidence that understanding the impact of referral hiring necessitates careful consideration of the behavioral consequences for the referrer.